Creative Economy Development at Silver Studio 76 Using Experience Economy for Silver Craft Preservation in Kotagede - Ahrman Sandikusumah; Sisilia Hangin; Mikke Susanto (TUMATA: Journal of Arts and Cultural Management, 2025)
The development of the creative economy based on silver craft at Silver Studio 76 in Kotagede, Yogyakarta, is carried out through the Experience Economy approach as a strategy for preserving local culture. The focus includes the implementation of the four dimensions of Experience Economy, which is: entertainment, education, aesthetic, and escapism in customer service, as well as the studio's role in supporting silver craft preservation. A qualitative case study method is employed to gain an in-depth understanding through interviews, observations, and secondary data analysis from social media and related documentation. This approach not only enhances the economic value of the products but also strengthens visitors emotional attachment and appreciation of Kotagede's cultural heritage. Challenges such as declining interest among younger generations, fluctuating tourist visits, limited skilled human resources, and rising production costs require ongoing innovation and optimization of digital marketing strategies. The findings contribute both conceptually and practically to developing experience based business models that sustain traditional craft industries while reinforcing local cultural preservation.